Helminth infection induces non-functional sensitization to house dust mites. - Virginie Doyen (PLoS ONE, 2021)
Background IgE characterizes the humoral response of allergic sensitization but less is known about what modulates its function and why some patients present clinical symptoms for a given IgE level and others do not. An IgE response also occurs during helminth diseases, independently of allergic symptoms. This response could be a model of non-functional IgE. Objective To study the IgE response against environmental allergens induced during natural helminth infection. Methods In 28 non allergic subjects from the periphery of Ho Chi Minh city with (H+, n = 18) and without helminth infection (H-, n = 10), we measured IgE and IgG4 against several components of Dermatophagoïdes pteronyssinus (Dpt) and Ascaris (a marker of immunization against nematodes), and determined the IgE component sensitization profile using microarray ISAC biochips. The functional ability of IgE to induce degranulation of cultured mast cells was evaluated in the presence of Dpt. Results Non allergic H+ subjects exhibited higher levels of IgE against Dpt compared to H- subjects. Dpt IgE were not functional in vitro and did not recognize usual Dpt major allergens. IgE recognized other component allergens that belong to different protein families, and most were glycosylated. Depletion of IgE recognizing carbohydrate cross-reactive determinant (CCD) did not induce a reduction in Dpt IgE. The Dpt IgG4 were not significantly different. Conclusion Helminth infections induced IgE against allergens such as Dpt and molecular components that belong to different sources as well as against CCD (such as β-1,2-xylose and/or ⍺-1,3-fucose substituted N-glycans). Dpt IgE were not able to induce degranulation of mast cells and were not explained by sensitization to usual major allergens or N-glycans.